Thermo-metallurgical simulation and performance evaluation of hybrid laser arc welding of chromium-molybdenum steel. (15th November 2021) - Du, Zhenglin; Sun, Xianchong; Ng, Fern Lan; Chew, Youxiang; Tan, Chaolin; Bi, Guijun
Graphical abstract: Highlights: Developed a thermo-metallurgical model for the hybrid laser arc welding to predict thermal and phase fields. Good agreement between predicted phase fractions with EBSD and hardness. Achieved an increase in hardness at the martensitic fusion zone despite having coarser grains. Obtained superior tensile properties in the fusion zone due to the presence of the martensite phase. Abstract: The phase constitution of the joint had a significant effect on the mechanical properties of the welded components. In this study, a thermo-metallurgical finite element model was developed for the hybrid laser arc welding process to predict the phase field and melt-pool dimensions of double-sided butt-welded chromium-molybdenum steel plates. The good agreement of the predicted phase fields and melt-pool dimensions with experimental results showed the potential of the numerical model to guide process development for the hybrid laser arc welding process. Further investigation via the Vickers hardness test and the bending test was performed on the fabricated welds. Tensile test results demonstrated superior tensile properties in the fusion zone, where specimen failure occurred within the base metal region. Microstructure analyses revealed the strengthening of the fusion zone by the formation of the martensite phase and grain refinement at the heat-affected zone (HAZ). No failure or cracks were observed in the samples after the bend test, indicating the high quality of the weld. Analysis of the HAZ of the weld overlap region indicated a reduction in the hardness and martensite volume percentage.